The Effect of Debt to Equity Ratio, Institutional Ownership, Size of the Board of Directors, and Size of the Board of Commissioners on Return on Assets in Energy Sector Companies - Ninda Ade Lutfiana; Ika Rosyada Fitriati (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
This study is a quantitative study that aims to examine and analyze the effect of debt to equity ratio, institutional ownership, board and board of commissioners Return on assets in energy sector companies listed on the Indonesia Stock Exchange in 2017-2021.The sampling method used in this research is purposive sampling. The research sample is 36 industries with 180 observations. Hypothesis testing in this study uses regression analysis with the E-Views 12.0 program. The results obtained (1) debt to equity ratio has a positive and significant effect on return on assets, (2) institutional ownership has a negative and significant effect on return on assets, (3) the board of directors has a negative and insignificant effect on return on assets, (4 ) the board of commissioners has a positive and significant effect on return on assets.